The SmartAG Partner: CCAFS East Africa Quarterly Newsletter, January - March 2015 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
We are pleased to share the eighth issue of the SmartAG Partner - CCAFS East Africa quarterly newsletter. We present initial results from the Nyando climate-smart villages in Kenya where the number of households eating one or no meals a day has reduced. Through a Nature commentary, read how various adaptation measures have brought this change. Also, find out how these lessons reach policy makers through learning visits to the villages. Many countries rely on default emission factors provided by the Intergovernmental Panel on Climate Change (IPCC) to make their greenhouse gas assessments. Read how a new state-of-the-art lab will enable accurate estimations in Kenya. Additionally, read through two recently published CCAFS working papers: Integrating indigenous knowledge with scientific forecasts in Lushoto, Tanzania - Working paper 103 and Agricultural adaptation and institutional responses to climate change vulnerability in Ethiopia - Working paper 106. From the field, we profile women farmers who are breaking gender barriers and taking the lead on climate-smart agriculture (CSA). Also read how community based organizations are promoting adoption of CSA practices in Kenyan drylands.